2000
DOI: 10.1517/13543784.9.6.1383
|View full text |Cite
|
Sign up to set email alerts
|

TNP-470: an angiogenesis inhibitor in clinical development for cancer

Abstract: TNP-470, an analogue of fumagillin, has been shown to inhibit angiogenesis in vitro and in vivo. In 1992, TNP-470 entered clinical development for cancer as an anti-angiogenic agent. It is currently in Phase I/II trials in Kaposi's sarcoma, renal cell carcinoma, brain cancer, breast cancer, cervical cancer and prostate cancer. In early clinical reports, TNP-470 is tolerated up to 177 mg/m(2) with neurotoxic effects (fatigue, vertigo, ataxia, and loss of concentration) being the principal dose limiting toxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(92 citation statements)
references
References 57 publications
1
90
0
Order By: Relevance
“…TNP-470 has been shown to inhibit tumor growth in a large number of syngeneic and human xenograft flank models. In clinical trials, it showed anecdotal tumor regression and disease stabilization in a few cases of lung and liver metastases (Castronovo and Belotti, 1996;Kruger and Figg, 2000). PPI-2458 is a novel, orally active agent of the fumagillin class of irreversible MetAP2 inhibitors and currently being evaluated in the clinic for cancer treatment (Hannig et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TNP-470 has been shown to inhibit tumor growth in a large number of syngeneic and human xenograft flank models. In clinical trials, it showed anecdotal tumor regression and disease stabilization in a few cases of lung and liver metastases (Castronovo and Belotti, 1996;Kruger and Figg, 2000). PPI-2458 is a novel, orally active agent of the fumagillin class of irreversible MetAP2 inhibitors and currently being evaluated in the clinic for cancer treatment (Hannig et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The prototype MetAP2 inhibitors fumagillin and TNP-470 are known as angiogenesis inhibitors in the literature (Ingber et al, 1990;Kusaka et al, 1994;Kruger and Figg, 2000), but they also posses antiproliferative activity in certain tumor lines (Wang et al, 2003a). To characterize the sensitivity of tumor cells to MetAP2 inhibition, we tested a panel of tumor lines with three distinct chemical classes of MetAP2 inhibitors: an irreversible inhibitor TNP-470 (Ingber et al, 1990;Griffith et al, 1997;Sin et al, 1997), a bestatin inhibitor A-357300 (Wang et al, 2003a) and a sulfonamide inhibitor A-800141 (Sheppard et al, 2006).…”
Section: Metap2 Inhibitors Directly Inhibit the Growth Of Cancer Cellsmentioning
confidence: 99%
“…TNP-470 inhibited the growth of primary and metastatic murine tumors and human xenografts such as breast cancer, neuroblastoma, ovarian cancer, prostate cancer, glioblastoma, neurofibrosarcoma and uterine sarcoma and led to a reduction in their vascularization5 -12 . The mechanism of the antiangiogenic activity of TNP-470 is still not completely clear, though proposed molecular mechanisms have suggested targeting methionine aminopeptidase (MetAP-2), affecting cell cycle through p53 activation, induction of p21(CIP/WAF) or preventing Rac1 activation 11, 13 -15. TNP-470 was one of the first antiangiogenic drugs to undergo clinical trials 16 . It demonstrated its ability to slow tumor progression or cause durable complete regression17 either given as a single agent, or in combination with other conventional chemotherapeutic drugs such as paclitaxel and carboplatin17 -23.…”
mentioning
confidence: 99%
“…A derivative of the natural product fumagillin, TNP470 has been shown to be safe and effective in the treatment of solid tumors in several animal studies and preclinical trials. TNP470 entered human clinical trials for the treatment of AIDS-related Kaposi's sarcoma, metastatic breast cancer, androgen-independent prostate cancer, pediatric solid tumors, lymphomas, acute leukemia, advanced squamous cell cancer of the cervix, and metastatic renal carcinoma (Dezube et al, 1998;Kruger and Figg, 2000;Kudelka et al, 1997). Several MetAP2 inhibitors were studied based on the inhibition of MetAP activity (Griffith et al, 1998;Antoine et al, 1994;Kusaka et al, 1994;Wang et al, 2000;Yeh et al, 2000;Zhang et al, 2000;Kim et al, 2004).…”
Section: Metap2 Inhibitorsmentioning
confidence: 99%